Preparation and in vitro evaluation of verapamil HCl and ibuprofen containing carrageenan beads - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
The objective of this study was to prepare and evaluate carrageenan beads as a controlled release system for a freely water Soluble drug verapamil hydrochloride and a slightly water soluble drug ibuprofen. Beads were prepared by ionotropic gelation method. The influence of formulation factors (drug content, polymer concentration, counterion type and concentration, outer phase volume) on the particle size, encapsulation efficiency and in vitro release characteristics of beads was investigated. The encapsulation efficiency of veraparnil HCl in the beads (34.8-71.1%) was higher than that of ibuprofen (23.6-58%). While about 30% of ibuprofen was released at 6 h. about 70% of veraparnil HCl was released in 5 h from the carrageenan beads prepared. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: carrageenan; beads; verapamil HCl; ibuprofen; controlled release; DRUG-RELEASE; MICROENCAPSULATION; POLYMER